Modern concepts of hepatic insufficiency, their advantages and faults: views of a general surgeon and transplantologist - N. Yu. Bayramov; A. A. Ibrahimova (Клінічна хірургія, 2021)
Modern concepts of hepatic insufficiency, their advantages and faults: views of a general surgeon and transplantologist